Experimental behavior of plain concrete under short-term creep in uniaxial compression and its relation to stiffness change. - Terán-Torres, Bernardo Tadeo; Juárez Alvarado, Cesar Antonio; Mendoza Rangel, Jose Manuel; Flores Vivian, Ismael; Cavazos de Lira, Diego; Hermosillo Mendoza, Roman; Bojorquez Calles, Miguel Dario; Lopez Yepez, Lucio Guillermo (Revista ALCONPAT, 2025)
In this study, specimens were tested under sustained axial compression loads to obtain their short-term creep behavior, i.e., over a period of one hour. The specimens were subjected to various loads (20%, 50%, and 80% of their capacity) at various ages (7, 28, and 90 days), recording the longitudinal and transverse strain over time. Subsequently, the specimens were tested to failure, obtaining the stress-strain curve, compressive strength, and modulus of elasticity. It was found that the specimens subjected to 20% load showed a slight increase in capacity and modulus of elasticity, while those subjected to 50% and 80% loads showed a decrease in capacity and modulus of elasticity for all ages.